Role of Technology Integration in Mergers & Acquisitions: A Case Study from the Embedded Software Industry - Kuppili, Murali Krishna; Donthala, Raghunatha Reddy (Prabandhan: Indian Journal of Management, 2015)
There is a huge potential for the embedded products in the global market. Mergers&Acquisitions certainly play a significant role to meet such high-growth market segments in the global environment. This paper follows a case study approach considering the merger of two embedded software companies located in different countries. The source company was interested to buy the target company to leverage the technological integration of both the companies, enabling development of a new cost optimized product. The focus of this paper is to examine the challenges of technology management just after the merger and the subsequent impact on business financials. It also describes the strategic solutions to address these issues and the successive financial results after implementation of these strategies.